Gestational outcomes of pregnant women who have had invasive prenatal testing for the prenatal diagnosis of spinal muscular atrophy - Atakan Tanacan; M.Sinan Beksac; Hayat Yurter; Burcu Soyak; Gokcen Orgul; Duygu Aydin Hakli; Tolga Celik; Gamze Bora; Ayse Nur Cakar; Haluk Topaloglu (South African Medical Association, 2018)
Background and Objective: To notify the importance of the prenatal diagnosis of spinal muscular atrophy (SMA) and to demonstrate the gestational outcomes of disease carrier pregnant women who have had invasive prenatal testing (IPT).Â Methods: WeÂ  retrospectively evaluated 113Â  pregnancies of 76 patients who were referred to the Division of Perinatal Medicine, Hacettepe University, Ankara for the prenatal diagnosis of SMA inbetween 2000 and 2015. We evaluted the screening results and gestational outcomes of the patients.Â  The pregnancy outcomes were compared to a control group of 179 patients .Beksac Obstetrics Index (BOI) was used for the comparison of obstetrical â€œhistories/backgroundsâ€ of the study and control groups.Results: Chorionic villus sampling (CVS) and amniocentesis (AC) were performed 83 (73.5%) and 30 (26.5%) cases respectively. 24 (21.2%) of the fetuses were found to be disease positive and and 23 of them were terminated. The median gestational day at birth, median birthweights and median BOI of the study and control groups wereÂ  compared and the difference was statistically significant (p<0.001),(p=0.002),(p=0.001).Conclusion: Prenatal diagnosis of SMA is very importantÂ  and nationwide specialÂ  antenatal care program must be run for better diagnosis and eradication of this genetical disorder.Key words: spinal muscular atrophy; prenatal diagnosis; invasive prenatal testing; genetic counseling